The royals - Kelley, Kitty (New York : Warner Books, 1997)
Meticulous research regarding the royal family - the private lives of Queen Elizabeth the Queen Mother, Queen Elizabeth II, Princess Margaret, Prince Philip, Prince Charles, Princess Diana, Prince Andrew and Sarah, the Duchess of York, as well as the forebears and predecessors.
Includes bibliographical references (p. 525-530) and index.
Keywords: Elizabeth -- II, -- Queen of Great Britain, -- 1926- -- Family; Windsor, House of; Queens -- Great Britain -- Biography